Utilisation of Machine Learning in Islamic Learning - Rahman, Rahman (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Machine learning is a branch of artificial intelligence that has become an important component in modern technology. This is due to its ability to develop computer programmes that can access and process data. In the context of Islamic learning, the application of machine learning can be a solution to improve the learning process and help in checking plagiarism. Purpose. This research aims to explore the utilisation of machine learning in Islamic learning. The specific objective is to understand the extent to which machine learning can facilitate Islamic religious education students in the learning process and assist in checking plagiarism. Method. This research uses a quantitative approach by collecting data through the Google Form application distributed to Islamic religious education students as research subjects. The data obtained is in the form of numbers which are then analysed to gain an understanding of the use of machine learning in Islamic learning. Results. The results showed that the use of machine learning can facilitate Islamic religious education students in learning and is effective in checking plagiarism. Students experience ease in understanding the material and the learning process becomes more efficient. Conclusion. Based on the research results, it can be concluded that machine learning has great potential in improving Islamic learning by solving various problems that may occur, such as difficulties in understanding the material and plagiarism problems. Nevertheless, this study has limitations in the scope of the subject which only focuses on Islamic religious education students. Therefore, the researcher recommends further research to expand the scope of subjects and deepen the understanding of the use of machine learning in various fields, as a reference for future research.